Protection against Aβ-induced neuronal damage by KU-32: PDHK1 inhibition as important target - Pal, Ranu; Hui, Dongwei; Menchen, Heather; Zhao, Huiping; Mozziconacci, Olivier; Wilkins, Heather; Blagg, Brian S. J.; Schöneich, Christian; Swerdlow, Russell H.; Michaelis, Mary L.; Michaelis, Elias K. (Frontiers in Aging Neuroscience, 2023)
A feature of most neurodegenerative diseases is the presence of 'mis-folded proteins' that form aggregates, suggesting suboptimal activity of neuronal molecular chaperones. Heat shock protein 90 (Hsp90) is the master regulator of cell responses to 'proteotoxic' stresses. Some Hsp90 modulators activate cascades leading to upregulation of additional chaperones.Novobiocin is a modulator at the C-terminal ATP-binding site of Hsp90. Of several novobiocin analogs synthesized and tested for protection against amyloid beta (Aβ)-induced neuronal death, 'KU-32' was the most potent in protecting primary neurons, but did not increase expression of other chaperones believed to help clear misfolded proteins. However, KU-32 reversed A-induced superoxide formation, activated Complex I of the electron transfer chain in mitochondria, and blocked the A-induced inhibition of Complex I in neuroblastoma cells. A mechanism for these effects of KU-32 on mitochondrial metabolism appeared to be the inhibition of pyruvate dehydrogenase kinase (PDHK), both in isolated brain mitochondria and in SH-SY5Y cells. PDHK inhibition by the classic enzyme inhibitor, dichloroacetate, led to neuroprotection from A25-35-induced cell injury similarly to KU-32. Inhibition of PDHK in neurons would lead to activation of the PDH complex, increased acetyl-CoA generation, stimulation of the tricarboxylic acid cycle and Complex I in the electron transfer chain, and enhanced oxidative phosphorylation. A focus of future studies may be on the potential value of PDHK as a target in AD therapy.